(untitled) (The Pakistan Development Review, 2015)
A key argument made by several economists with respect to decentralisation reform is that it can reduce poverty. This assertion is based on the view that it leads to improvements in public sector services delivery. The efficient provision of public goods by the local governments may occur because of their ability to take into account local determinants while providing services, such as health and education [Oates (1972)]. It may also be due to competition, as local governments encourage the provision of efficient public services to, and lower tax burdens on the lower strata of society [Brennan and Buchanan (1980)].